Re-examing purchasing power parity for East-Asian currencies : 1976-2002. - Baharumshah, Ahmad Zubaidi; Chan, Tze Haw; Fountas, Stilianos (Taylor & Francis, 2008)
We investigate the behaviour of real exchange rates of six East-Asian countries in relation to their two major trading partners – the United States and Japan. These countries, except, Singapore were affected by the financial crisis of the fall 1997. Using monthly frequency data from 1976 to 2002 and the autoregressive distributed lag (ARDL) cointegration procedure we test for the long-run purchasing power parity (PPP) hypothesis. We find no evidence for the weak form of PPP in the pre-crisis period, but strong evidence in the post-crisis period. For the post-crisis period, we also find very small persistence of PPP deviations as indicated by very small half-lives (<7 months) and narrow confidence intervals with an upper bound of 1 year or less in most countries. Our findings reveal that the East Asian countries are returning to some form of PPP-oriented rule as a basis for their exchange rate policies.